2002
DOI: 10.1097/00000637-200208000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Circumflex Femoral Arterial System and Perforators of the Anterolateral Thigh Flap: An Anatomic Study

Abstract: The authors performed an anatomic study on 16 thighs of 11 fresh white cadavers at the Ludwig-Maximilian University of Munchen, Germany. They analyzed the anatomic pattern and caliber of both the lateral circumflex femoral arterial system and the perforators nourishing the anterolateral thigh flap. They found regularly a majority of musculocutaneous perforators, mainly in the central third of the thigh, arising from the descending branch of the lateral circumflex femoral artery. Despite the small number of cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 14 publications
5
61
1
1
Order By: Relevance
“…The average skin area dyed on the TFL flap, vascularised by the perforating branches of the ascending branch of the LCFA was 20 × 24 cm -similar to the data from the literature [14,16,35]. The distance of the far distal point of the dyed skin area from the anterior superior iliac spine was 24 cm in average, which is a point of orientation in length of the rotation arc of the flap in surgery [14].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The average skin area dyed on the TFL flap, vascularised by the perforating branches of the ascending branch of the LCFA was 20 × 24 cm -similar to the data from the literature [14,16,35]. The distance of the far distal point of the dyed skin area from the anterior superior iliac spine was 24 cm in average, which is a point of orientation in length of the rotation arc of the flap in surgery [14].…”
Section: Discussionsupporting
confidence: 79%
“…In some studies it was shown that they both arise from FA in different percentages (0.5%, 0.9% and 1.5%) [2,9,34]. Our material did not show the origin of the ascending and the descending branches from any other blood vessel, which has been presented by some other research [29,35].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Detailed anatomical knowledge about the LCFA is useful in a number of clinical procedures, including aortopopliteal bypass [10,29], anterolateral thigh flaps [33], and coronary artery bypass grafting [8], thus giving its normal and variant anatomy a high degree of clinical significance. Furthermore, its branches may also be used in various procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The LCFA is used in a diverse number of clinical procedures, including aortopopliteal bypass [10,29], anterolateral thigh flaps [33] and coronary artery bypass grafting [8], giving its normal and variant anatomy a high degree of clinical significance. Furthermore, its branches may also be used in various procedures, for example its ascending branch is often used for vascularised iliac transplant, and its descending branch can be used as a collateral for an obstructed superficial femoral artery (SFA) [12,32].…”
Section: Introductionmentioning
confidence: 99%